Discharge calculation of paleochannels on the alluvial fan of the Maros river, Hungary - Sümeghy, Borbála; Kiss, Tímea (Journal of Environmental Geography, 2011)
The aim of the study was to identify the abandoned channels on the alluvial fan of the Maros River and to calculate their paleodischarge. As the first step of the investigation regional equations had to be made for discharge calculations based on the earliest available discharge data for the rivers of the Tisza catchment in Hungary. Equations between discharge and channel parameters were created with high correlation coefficient. Then the paleochannels were identified on the Hungarian part of the alluvial fan. The paleochannel generations are located in continuous zones with well defined boundaries. The density of the abandoned channels varies on the alluvial fan, as some areas densely covered by channels and on other areas almost free of paleochannels. Braided, meandering and misfit channels were separated, but only the morphometry of the meandering and misfit channels were measured (width, ratio of curvature, half-wavelength and cord-length). Based on these morphometric parameters and the discharge equations the mean discharge of the channels was calculated. The greatest discharge was around 6300 m3/s while the smallest was 31 m3/s. However, several abandoned meandering channels had slightly greater bankfull discharge (700-900 m3/s) as the present-day Maros River.